1997
DOI: 10.1006/nimg.1996.0232
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Responses to Lexical and Nonlexical Visual Stimuli in Occipital Cortex: A Functional Magnetic Resonance Imaging Study

Abstract: Stimulus-related changes in cerebral blood oxygenation were measured using high-resolution functional magnetic resonance imaging sequentially covering visual occipital areas in contiguous sections. During dynamic imaging, healthy subjects silently viewed pseudowords, single false fonts, or length-matched strings of the same false fonts. The paradigm consisted of a sixfold alternation of an activation and a control task. With pseudowords as activation vs single false fonts as control, responses were seen mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 7 publications
(21 reference statements)
4
39
0
Order By: Relevance
“…1) or modulation of activation (Fig. 2) in the posterior superior temporal lobe, a region often activated by words and pronounceable nonwords in comparison to unpronounceable strings (Booth et al, 2002;Herbster et al, 1997;Howard et al, 1992;Indefrey et al, 1997;Price et al, 1996;Tagamets et al, 2000). We propose that this posterior superior temporal region (centered on the posterior superior temporal sulcus) is sensitive to the pronounceability of letter strings, consistent with its hypothesized role in phonological access and visual-auditory integration (Callan et al, 2005;Hickok et al, 2000;Indefrey and Levelt, 2000;Van Atteveldt et al, 2004;Wise et al, 2001).…”
Section: Discussionsupporting
confidence: 60%
“…1) or modulation of activation (Fig. 2) in the posterior superior temporal lobe, a region often activated by words and pronounceable nonwords in comparison to unpronounceable strings (Booth et al, 2002;Herbster et al, 1997;Howard et al, 1992;Indefrey et al, 1997;Price et al, 1996;Tagamets et al, 2000). We propose that this posterior superior temporal region (centered on the posterior superior temporal sulcus) is sensitive to the pronounceability of letter strings, consistent with its hypothesized role in phonological access and visual-auditory integration (Callan et al, 2005;Hickok et al, 2000;Indefrey and Levelt, 2000;Van Atteveldt et al, 2004;Wise et al, 2001).…”
Section: Discussionsupporting
confidence: 60%
“…Studies with a 150 ms or shorter duration generally reported more activation for words and word-like stimuli, whereas studies with a duration as long as 750 ms did not show such a pattern (Indefrey et al, 1997) and sometimes showed a reversed pattern (Xue et al, 2006). In two PET studies (Price et al, 1996(Price et al, , 1994, Price and her colleagues systematically explored the effect of presentation duration on word processing.…”
Section: The Effect Of Presentation Durationmentioning
confidence: 99%
“…Two recent studies of reading, one using PET (Mechelli, Humphreys, Mayall, Olson, & Price, 2000) and one using fMRI (Indefrey et al, 1997), revealed monotonic increases in signal strength as a function of word length. These effects were visible in the midline posterior occipital cortex, bordering on the fusiform gyrus.…”
Section: Letter String Lengthmentioning
confidence: 99%